2020
DOI: 10.1016/j.str.2020.02.007
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Conformation for K48 Ubiquitin Chains Revealed by the hRpn2:Rpn13:K48-Diubiquitin Structure

Abstract: Highlights d Chemical origin of Rpn13 preference for K48-linked ubiquitin chains revealed d NMR demonstrates highly dynamic interactions between hRpn2:hRpn13 and K48-diubiquitin d K48-diubiquitin adopts a dynamic, extended conformation that hRpn13 selects d Structure of hRpn2:Rpn13 bound to K48-diubiquitin described

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 70 publications
0
25
1
Order By: Relevance
“…2E), perhaps because the loss at the proteasome is compensated by correlative accumulation of ubiquitinated substrates that failed to be recruited or retained at proteasomes for degradation. Nonetheless, the data presented here do not We recently found that hRpn13 exchanges between the two ubiquitin moieties of K48-linked diubiquitin and maintains an extended conformational state for the ubiquitin chain(56), which would facilitate further interactions with other ubiquitin-binding sites of weaker affinity, such as in hRpn1. Moreover, hRpn13 is at an apical location of the RP (57-60), which is likely to be ideal for recruitment of proteins to the proteasome.…”
contrasting
confidence: 54%
“…2E), perhaps because the loss at the proteasome is compensated by correlative accumulation of ubiquitinated substrates that failed to be recruited or retained at proteasomes for degradation. Nonetheless, the data presented here do not We recently found that hRpn13 exchanges between the two ubiquitin moieties of K48-linked diubiquitin and maintains an extended conformational state for the ubiquitin chain(56), which would facilitate further interactions with other ubiquitin-binding sites of weaker affinity, such as in hRpn1. Moreover, hRpn13 is at an apical location of the RP (57-60), which is likely to be ideal for recruitment of proteins to the proteasome.…”
contrasting
confidence: 54%
“…The PRU domain of RPN13 selectively recognizes a dynamic, extended conformation of Lys48-linked diubiquitin via loops extending from the β-strands in the PRU domain and exhibits ∼90 nM K D for Lys48-linked diubiquitin. In the proteasome, the PRU domain binds a flexible C-terminal region of RPN2, which emanates from its LRR-like toroidal domain (Chen et al 2010;Sakata et al 2012;Lu et al 2017aLu et al , 2020. The recruitment of RPN13 near the toroid apex of RPN2 positions its PRU domain about four-ubiquitin away from the entrance of the ATPase ring, which is comparable to the distance from the ubiquitin-binding sites in RPN1 and RPN10 (Lu et al 2020).…”
Section: Rpn13mentioning
confidence: 99%
“…In the proteasome, the PRU domain binds a flexible C-terminal region of RPN2, which emanates from its LRR-like toroidal domain (Chen et al 2010;Sakata et al 2012;Lu et al 2017aLu et al , 2020. The recruitment of RPN13 near the toroid apex of RPN2 positions its PRU domain about four-ubiquitin away from the entrance of the ATPase ring, which is comparable to the distance from the ubiquitin-binding sites in RPN1 and RPN10 (Lu et al 2020). The PRU domain of human RPN13 is connected by a flexible linker to a C-terminal helical DEUBAD (DEUBiquitinase ADaptor) domain that recruits and activates the DUB UCH37 (Lu et al 2017a;Sahtoe et al 2015;Hamazaki et al 2006;Qiu et al 2006;Yao et al 2006).…”
Section: Rpn13mentioning
confidence: 99%
See 2 more Smart Citations